Snapshot of Rural Special Education: Strategies to Attract and Retain Special Education Teachers - Jerrie Brooks; Jacqueline Lubin; Stephanie Weigel (The Advocate, 2024)
This study’s purpose was to obtain a current picture of special education in rural districts to understand what can be done to attract special education teachers and what can be done to keep them in rural regions. A survey adapted from Berry (2012) was administered via Qualtrics to special education teachers in rural Midwest US. Sixty percent of the special education teachers responded to the survey. The results revealed factors that enticed and retained teachers to rural settings included the provision of support, financial incentives, job-related factors, and rural initiatives. Although some findings revealed the factors that attracted and retained special educators were somewhat akin to factors in previous studies, slight variations were found such as broadened viewpoints of how financial benefits and support can be used to boost recruitment and retention. The results also showed that more work may be needed to address job-related factors and rural initiatives. Implications for the field are discussed.
Keywords: rural special education teachers; retention; attraction